Effect of goat's alpha-s1 casein genotype on diet selection in a free choice feeding system - Avondo M.; Pagano R.; Guastella A.M.; Criscione A.; Di Gloria M.; Valenti B.; Lutri L.; Pennisi P. (Nutritional and foraging ecology of sheep and goats, 2009)
In goats, alpha-s1 casein polymorphism is related to different rates of protein synthesis. Two genetic variants, A and F, have been identified as strong and weak alleles based on a production of 3.5 and 0.45 g/l of alpha-s1 casein per allele. The aim of the trial was to test if goats can self-regulate their diet as a function of the genetic aptitude to produce milk at different casein levels. Two groups of 8 animals, homozygous for strong (AA) or weak (FF) alleles were selected from a flock of 120 Girgentana lactating goats. Animals were housed in individual pens. Using a manger subdivided into 5 separate containers, the goats were offered, daily for 3 weeks, 1.5 kg of alfalfa pelleted hay, two sources of starch (0.7 kg of whole barley, rapidly degradable and 0.7 kg of whole maize, slowly degradable) and two sources of protein (0.7 kg of whole faba bean, more rapidly degradable and 0.7 kg of pelleted sunflower cake, less rapidly degradable). Individual intake for each feed was measured daily; individual feeding behaviour was measured for 7 days using a 24 hour video surveillance system; milk characteristics were measured every three days. As expected, protein and casein were significantly higher in AA group than in FF group (protein: 3.50 ± 0.17% vs 3.18 ± 0.16%; casein: 2.70 ± 0.14% vs 2.40 ± 0.17%; P < 0.01), whereas milk urea was higher in FF group (59.7 ± 8.0 vs 48.8 ± 4.4 mg/dl; P < 0.01). Total DM intake and chemical composition of the selected diets were similar between groups. However, goats carrying AA alleles had a tendency to reduce the concentrate/forage ratio (1.68 ± 0.28 vs 1.97 ± 0.34) and to select less faba bean (9.0 ± 1.9% vs 12.8 ± 3.3%; P = 0.016) and more maize (22.9 ± 2.6% vs 19.9 ± 2.5%; P = 0.03) than goats carrying the FF alleles. This self regulation of the diet could partially explain the differences in milk composition.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)